Marketing Problems in Agriculture Export of the Republic of Uzbekistan - Musayeva Shoira Azimovna; Usmonova Dilfuza Ilkhomovna; Usmanov Farzod Shokhrukhovich (International Journal on Integrated Education, 2021)
This article examines the current state of the efficiency of the agricultural production and marketing system, the existing problems and the current state of the impact of the marketing system on pricing and product management, and analyzes the supply of products to consumer markets. The analysis shows that farmers and private farms specialize in producing more of the same type of food.